2017
DOI: 10.1590/1414-431x20176048
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between uric acid levels and risk of chronic kidney disease in a retrospective cohort of Brazilian workers

Abstract: Uric acid (UA) levels are increased in patients with kidney dysfunction. We analyzed the association between asymptomatic hyperuricemia and new-onset chronic kidney disease (CKD). A retrospective cohort study was designed to collect data from employees of an energy generation and distribution company in the city of Rio de Janeiro, Brazil, who had undergone the company’s annual medical checkup from 2008 to 2014. People with ≤2 years of follow-up, with baseline estimated glomerular filtration rate (eGFR) <60 mL·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
“…The association between uric acid and kidney disease has been previously investigated. Numerous studies reported a positive association between the levels of circulating uric acid and the risk of CKD progression [4][5][6][7][8][9][10][11][12], but this was negated in other studies [13][14][15]. Observational studies experience residual problems of poorly measured or unmeasured confounding factors and reverse causality when the disease process has a long latency period.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia or high serum uric acid (SUA) levels have been linked to obesity, 1,2 fatty liver, type 2 diabetes, 3 and renal injury 4 . Moreover, research has indicated a contributory role of uric acid (UA) in metabolic syndrome, which is characterized by dyslipidemia, insulin resistance, and hypertension 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 28 Moreover, there are several studies showing that diabetes is associated with the development of increased albuminuria and faster progression of CKD. 28 30–32 Evidence from other Latin American countries 30–32 suggests that diabetes and worse glycaemic control are significant predictors for increased albuminuria, faster progression of CKD and need for RRT. On the other hand, a meta-analysis which analysed the risk factors for development and progression of CKD, showed that diabetes was marginally predictive of progression from late-stage CKD to ESKD (HR: 1.16, 95% CI: 0.98 to 1.38; p = 0.08).…”
Section: Discussionmentioning
confidence: 99%